2013
DOI: 10.1073/pnas.1316032110
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin-3 regulates integrin activation and adhesion reinforcement of effector T cells

Abstract: Activated T cells use very late antigen-4/α4β1 integrin for capture, rolling on, and firm adhesion to endothelial cells, and use leukocyte function-associated antigen-1/αLβ2 integrin for subsequent crawling and extravasation. Inhibition of α4β1 is sufficient to prevent extravasation of activated T cells and is successfully used to combat autoimmune diseases, such as multiple sclerosis. Here we show that effector T cells lacking the integrin activator Kindlin-3 extravasate and induce experimental autoimmune enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 34 publications
5
50
0
Order By: Relevance
“…The role of kindlin-3 in the activation and functions of leukocyte integrins was corroborated with intravital imaging of TNF-α-stimulated cremaster-muscle venules, which revealed that adhesion of leukocytes to inflamed endothelial cells was dramatically impaired (Moser et al, 2009a). In effector T cells, the kindlin-3-mediated integrin activation step appears to be particularly important when the expression levels of integrin ligands on endothelial cells are low (Moretti et al, 2013;Morrison et al, 2013). Hence, in experimental autoimmune encephalitis (EAE), a model for multiple sclerosis with a high expression of integrin ligand in the inflamed tissue, inhibition of kindlin-3 is probably not sufficient to block extravasation of autoreactive T cells and disease progression (Moretti et al, 2013).…”
Section: Kindlin-3 In Hematopoietic Dysfunctions and Lad IIImentioning
confidence: 81%
See 1 more Smart Citation
“…The role of kindlin-3 in the activation and functions of leukocyte integrins was corroborated with intravital imaging of TNF-α-stimulated cremaster-muscle venules, which revealed that adhesion of leukocytes to inflamed endothelial cells was dramatically impaired (Moser et al, 2009a). In effector T cells, the kindlin-3-mediated integrin activation step appears to be particularly important when the expression levels of integrin ligands on endothelial cells are low (Moretti et al, 2013;Morrison et al, 2013). Hence, in experimental autoimmune encephalitis (EAE), a model for multiple sclerosis with a high expression of integrin ligand in the inflamed tissue, inhibition of kindlin-3 is probably not sufficient to block extravasation of autoreactive T cells and disease progression (Moretti et al, 2013).…”
Section: Kindlin-3 In Hematopoietic Dysfunctions and Lad IIImentioning
confidence: 81%
“…In effector T cells, the kindlin-3-mediated integrin activation step appears to be particularly important when the expression levels of integrin ligands on endothelial cells are low (Moretti et al, 2013;Morrison et al, 2013). Hence, in experimental autoimmune encephalitis (EAE), a model for multiple sclerosis with a high expression of integrin ligand in the inflamed tissue, inhibition of kindlin-3 is probably not sufficient to block extravasation of autoreactive T cells and disease progression (Moretti et al, 2013). Kindlin-3 is also required for B-cell adhesion under flow (Willenbrock et al, 2013), trafficking into lymph nodes and immunoglobulin expression (Morrison et al, 2015).…”
Section: Kindlin-3 In Hematopoietic Dysfunctions and Lad IIImentioning
confidence: 99%
“…Similarly, deletion of the cytoskeletal regulators Rap1, RIAM, talin, or RAPL impair chemokine-stimulated ICAM-1 adhesion and naïve T-cell trafficking (52)(53)(54), whereas CRK proteins regulate T-cell adhesion, chemotaxis, and diapedesis, leading to reduced T-cell trafficking selectively to inflamed tissues (55). In contrast, recent reports show that Kindlin-3 is not required for diapedesis, although it has been shown to play an important role in adhesion and CNS trafficking more generally (56,57).…”
Section: Discussionmentioning
confidence: 99%
“…Kindlins provide a physical link between the integrin and the cortical actin cytoskeleton and are thought to be involved in integrin conformational change to the active, fully open state, as well as contributing to downstream integrin signaling (17). In lymphocytes, kindlin-3 binds LFA-1 and is essential for firm adhesion of both T and B cells (18)(19)(20), and it stabilizes integrin/ligand interactions in T cells following TCR engagement in vitro (21). Meanwhile, 14-3-3 proteins bind to the TTT site when one or more of the T residues are phosphorylated (e.g., after T cell activation by phorbol esters) and initiate downstream integrin signaling (22).…”
Section: Discussionmentioning
confidence: 99%